All you need to know before you start school - Brooks, Felicity; Aizen, Marina; Allen, Francesca (England Usborne, 2017)
This work follows five animal friends who have just started school. An introduction to the school day, from getting dressed in the morning to home time, this is interspersed with early years educational concepts such as shapes, colours, opposites, numbers, weather and seasons, senses, nature words and letter recognition
Linguistic notions
Keywords: First day of school; Picture books; Vocabulary